Answer:
2*(-3)= -6
Step-by-step explanation:
I do not see how "a*b=2a-3b" would change the fact 2 times negative 3 is -6
First you must know that is i∧2= -1
x∧3-4x∧2+4x-16 = x∧2 (x-4) + 4 (x-4) = (x-4) (x∧2+4) = (x-4) (x∧2-(-4)) =
= (x-4) (x∧2-(-1) *4) = (x-4) (x∧2- i∧2*2∧2) = (x-4) (x∧2-(2i)∧2) = (x-4) (x-2i) (x+2i)
Good luck!!!
Answer: The correct answer is 27/26 or 1 11/16
Step- by-step explanation:
Answer:
y = -1/2x +1/2
Step-by-step explanation:
Point B is 4 up and 2 over from point A. So, the midpoint will be 4/2 = 2 up and 2/2 = 1 over, at (1, 0).
The ratio of rise to run between A and B is ...
m = rise/run = 4/2 = 2
The perpendicular line will have a slope that is the opposite reciprocal of this, -1/2.
Then the point-slope equation for the perpendicular bisector is ...
y -k = m(x -h) . . . . . line with slope m through point (h, k)
y -0 = -1/2(x -1) . . . .line with slope -1/2 through point (1, 0)
y = -1/2x +1/2 . . . . simplified to slope-intercept form